Easy, Quality of Service, and Timeliness of Delivery to Customer Satisfaction - Faizal Ridho; Sri Hartono; Istiqomah Istiqomah (Almana : Jurnal Manajemen dan Bisnis, 2021)
The Internet makes it easy for users to trade with people. This is what causes many companies to compete to create quality online services or e-commerce services that consumers can trust to simplify and add value to the products they offer so that they can be cheaper and more efficient. The purpose of this study was to determine the effect of easy, service quality, and timeliness of delivery on customer satisfaction in online shopping store users of the Surakarta UNIBA student application. This research is quantitative descriptive. The population in this study were the users of the online shopping store, Surakarta, UNIBA students, totaling 911 students. The sample uses 10% of the total population and the results are 91.1 students and then rounded up to 100 students. Easy, Quality of Service and Timeliness of Delivery have a simultaneous and significant effect on Customer Satisfaction in the online shopping application Tokopedia. Based on the t-test, Easy has a positive and significant effect on Customer Satisfaction in the Tokopedia online shopping application. Service Quality has a positive and significant effect on Customer Satisfaction in the online shopping application Tokopedia. Timeliness of Delivery has a positive and significant effect on Customer Satisfaction in the online shopping application Tokopedia.